NEGOSIASI HETERONORMATIVITAS PADA PERFORMATIVITAS TRANSGENDER DALAM FILM LOVELY MAN - Nadya Afdholy (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2019)
This study aims to reveal heteronormativity in the Lovely Man movie by director Teddy Soeriaatmadja by using narrative structure theory from Tzvetan Todorov and the concept initiated by Judith Butler. Heteronormative values that appear in the film directed by Teddy Soeriaatmadja are seen through dialogue between characters in each scene that are divided into three; (1) equilibrium/plenitude, (2) disruption, disequilibrium/disrupting force, and (3) opposing force. This research uses qualitative method by using approach of narrative analysis of model Tzvetan Todorov. The data used for this research is the film of Lovely Man by director Teddy Soeriaatmadja itself. This study uses data collection techniques with observation and literature study, as well as using data collection techniques with data reduction, interpretation, and conclusions. The results of this study indicate that there is a concept of heteronormative values reflected through heterosexuals who are considered to damage the stability of transvestite life, so that heterosexuals are considered as 'the other' heteronormative. Keywords: Film, Lovely Man, Heteronormativity, Other.